The Equilibrium Distributions of Value for Risky Stocks and Bonds - Johannes, Ronald (IMF Working Papers; Working Paper ;, 2001)
Within a unified theory for stocks and corporate bonds, based on dynamic optimization by investors, this paper derives analytical expressions for the momentary distributions of expected price, respectively known to approximate lognormal with systematic deviations (high peak, fat tail) and double exponential (for credit risk). Market equilibrium is regarded as a dynamic equilibrium characterized by a time-invariant probability distribution over microfinancial states, marginal redistributions of portfolios are regarded as indistinguishable, and real and fiat assets are regarded as essentially distinct. The formalism provides a basis for decomposing value changes by market fundamentals, investor sentiment, and investor acquisition of securities.